Horseshoe bat species recorded in the mangrove ecosystem of the Cat Ba National Park, Northern Vietnam - Thong, Vu Dinh; Nha, Pham Van; Tien, Pham Duc; Luong, Nguyen Thanh; Dang, Nguyen Xuan; Nghia, Nguyen Xuan; Southaphanh, Schanh; Thongphachanh, Ladthavong; Dung, Do Thuy; Khu, Nguyen Xuan; et al. (Academia Journal of Biology, 2021)
Cat Ba National Park is the core zone of the Cat Ba Archipelago Biosphere Reserve. It contains quite diverse and unique ecosystems including 776 ha of mangrove forest. Although bats of the park were included in many publications, none were recorded from the mangrove ecosystem. We recently conducted field surveys through the wetland areas of the park and recorded three horseshoe bat species: Marshall’s horseshoe bat (Rhinolophus marshalli), Pearson’s horseshoe bat (Rhinolophus pearsonii), and the least horseshoe bat (R. pusillus). Of these, R. pearsonii is the most common species. We here provide morpholocal and acoustic features of each species with notes on the importance of the mangrove forest in the park for bat research and conservation.